Institutional Strategies in Vocational Railway Schools of the Ministry of Transportation in the Era of the Industrial Revolution 4.0 - Nopriyanto, Windi; Handoko, V.Rudy; Maduwinarti, Ayun; Alamsyah, Alamsyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Indonesian Railway Polytechnic (PPI) Madiun plays a crucial role in preparing skilled workers for the railway industry. However, challenges such as a gap between the curriculum and industry needs, a lack of qualified lecturers in technology, insufficient educational facilities, and limited industry partnerships have emerged in the era of the Industrial Revolution 4.0. This study uses a SWOT analysis to explore strategies for institutional development at PPI Madiun. Data collection methods include interviews, observations, and document analysis. Despite challenges, PPI Madiun has significant opportunities to excel by enhancing its curriculum, improving faculty skills, expanding industry partnerships, and fostering innovation. Adaptive strategies are essential to ensure PPI Madiun produces competent graduates ready for the industry 4.0 challenges.